Hastings Alumni and Fresno County Bar Association Joint Luncheon with California Supreme Court Justice Wiley Manuel - Watkins, Howard::::::::: (1979)
Howard Watkins, Baxter Richardson, Justice Wiley Manuel, Judge Hollis Best, and Hastings Alumni Director Libby Strobe